Cloud-Based Architectural Framework for Scalable and High-Performance Smart Applications - Kamal Khan; Zamil Rahman; Amrita Khan; Anamika Roy; Jhon Kabir (Eastasouth Institute, 2023)
The rapid evolution of smart applications, driven by advancements in the Internet of Things (IoT), artificial intelligence (AI), and big data analytics, has significantly increased the demand for scalable and high-performance computing infrastructures. Traditional architecture often struggles to meet these requirements due to limitations in resource scalability, processing efficiency, and system flexibility. The proposed framework emphasizes a layered architecture consisting of data acquisition, processing, service management, and application layers, ensuring efficient data flow and resource utilization. It leverages cloud-native principles to enable horizontal scalability, fault tolerance, and continuous deployment. Additionally, the integration of edge computing reduces latency by processing time-sensitive data closer to the source, thereby improving real-time responsiveness. Performance optimization techniques, including auto-scaling and load balancing, are incorporated to ensure consistent system performance under varying workloads. The framework also addresses critical challenges such as interoperability, security, and resource management by incorporating standardized interfaces and intelligent orchestration mechanisms. Experimental analysis and conceptual evaluation indicate that the proposed architecture significantly enhances system scalability, reduces latency, and improves overall application performance compared to traditional models. This study contributes to the field by providing a comprehensive architectural model that aligns with the evolving requirements of modern smart applications. The findings demonstrate that cloud-based frameworks, when combined with emerging technologies, can effectively support large-scale, high-performance systems. The proposed approach offers valuable insights for researchers and practitioners in designing next-generation smart application infrastructures.